(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Anxiety disorders, one of the most common mental disorders, have been known to significantly impair different aspects of an affected person’s life, including their self-esteem, self-image, and self-concept. Previous studies have shown a link between somatic symptom disorder (SSD) and higher anxiety levels. The aim of this study was to assess the self-esteem and self-concept of somatic symptom disorder patients in comorbid with anxiety disorders. Materials and Methods: This cross-sectional study was conducted on 86 anxiety disorder patients who after a thorough clinical examination and psychiatric interview, were divided into two groups: 43 patients who also suffered from somatic symptom disorder, and 43 people without somatic symptom disorder. The self-esteem, self-concept, and anxiety level of the participants were assessed using the Coopersmith Self-Esteem Inventory, the Beck Self-Concept Test, and the Hamilton Anxiety rating Scale. Data were analyzed using SPSS 26 software. In all of the tests, 0.05 was considered as the cut off for significance. Results: The findings showed a significantly lower self-esteem level in the somatic symptom disorder group compared to those not suffering from this disorder. In addition, somatic symptom disorder patients were suffering from significantly higher levels of anxiety compared to the group without SSD. However, no significant difference was observed between the two groups in terms of self-concept. Conclusion: These results suggest that somatic symptom disorder, can negatively impact the affected individual’s self-esteem and body image which might further contribute to their emotional burden and suffering. The proper assessment and treatment of low self-esteem in these persons could be useful and help prevent other negative outcomes.